Distribution and species composition of lepidopterous maize borers in southern Nigeria - Bosque Pérez, N.A.; Mareck, J.H. (Cambridge University Press, 1990)
The distribution and species composition of lepidopterous maize borers was studied in six locations in southern Nigeria during the second planting season (August-November) of 1985 and 1986. Sesamia calamistis Hampson (Noctuidae) and Eldana saccharina Walker (Pyralidae) were the stem borers most abundantly found in the locations sampled. S. calamistis was the dominant species up to eight weeks after planting in all locations. E. saccharina was the most abundant species from nine weeks after planting onwards, except at Umuahia where S. calamistis always comprised over 50% of the borer population. Mussidia nigrivenella Ragonot (Pyralidae) was found attacking maize ears in all locations, while Busseola fusca Fuller (Noctuidae) was found only at Idah and Alabata, and even there constituted only a small proportion of the population. Other borer species found were Coniesta (= Acigona) ignefusalis (Hampson) (Pyralidae) and Cryptophlebia species (Olethreutidae).